1997
DOI: 10.1364/ao.36.006011
|View full text |Cite
|
Sign up to set email alerts
|

Lidar profiles of fish schools

Abstract: A lidar system was used in a seawater tank to measure the average diffuse reflectivity of live sardines. Diffuse reflectivity was measured to be 10 % for a copolarized laser return and 3 % for a cross-polarized return. We used these calibration measurements to infer the density of sardines in areas of the Southern California Bight from vertical profiles obtained with the lidar mounted on a ship. Within schools densities up to ~0.01 kg m-3 were observed. During hourly survey periods total habitat densities up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 3 publications
0
35
0
8
Order By: Relevance
“…The narrow filter minimizes the amount of background light entering the receiver, but effectively limits the penetration depth of laser light (Gordon, 1982). A polarizer in front of the telescope selects the cross-polarized component of the reflected light, thus maximizing contrast between fish and smaller light-scattering particles (Churnside et al, 1997;Lewis et al, 1999). The telescope collects the light onto an interference filter to reject background light.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The narrow filter minimizes the amount of background light entering the receiver, but effectively limits the penetration depth of laser light (Gordon, 1982). A polarizer in front of the telescope selects the cross-polarized component of the reflected light, thus maximizing contrast between fish and smaller light-scattering particles (Churnside et al, 1997;Lewis et al, 1999). The telescope collects the light onto an interference filter to reject background light.…”
Section: Methodsmentioning
confidence: 99%
“…The FLOE system penetrates depths up to 50 m, and has been used off the coast of California to survey anchovy and sardine (Hunter and Churnside, 1995;Churnside et al, 1997;Lo et al, 2000), and has more recently been used to measure plankton, squid, and marine mammals (Churnside et al, 2001a). Comparisons of lidar with acoustic data have been very encouraging, and these methods can produce similar results (Churnside et al, 2001b; Figure 1).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…This was determined during ship tests of the lidar, where the depolarization of the return from fish was about 30% and the depolarization of the water return was only about 10%. 16 These results, however, represent only 1 species of fish Note that the reflection from the air-water interface preserves polarization, and is not detected by our profiling receiver. The sea-surface return used for timing is actually the return from particles just below the surface.…”
Section: Lidar Systemmentioning
confidence: 84%
“…Prior work where lidar data were compared with echosounder data has shown that fish typically appear as long spikes because of the long laser pulse. 19,41,69,70 Potential spawning sites are identified by considering the location and depth of the fish. No automated algorithms for freshwater fish identification currently exist, and this is an area for future research.…”
Section: Resultsmentioning
confidence: 99%